Epistaxis in racehorses: risk factors and effects on career. Issue 5 (25th April 2013) - Langford, JL; Thomson, PC; Knight, PK
<x xml:space="preserve">Abstract</x> Objective To profile Thoroughbreds that incurred a ban under Australian Rule of Racing 53A on New South Wales racetracks between August 1999 and July 2008, determine the effect on their careers and identify the factors that predict whether these horses would race again or experience a recurrence of epistaxis. Methods Differences between horses that did or did not return to racing and did or did not suffer recurrent epistaxis were determined. Backwards stepwise logistic regression was used to identify variables predicting a return to racing and recurrence of epistaxis. Results The mean (± SD) age at the first episode of epistaxis was 4.90 ± 1.28 years. Males that bled were older, had more career starts and were more likely to race again than females. Horses that were retired from racing after the first episode of epistaxis were older than horses that continued to race. Variables that were significant predictors of retirement were: age at the first episode of epistaxis, sex, percentage of winning starts before the first episode of epistaxis, percentage of placed starts before the first episode of epistaxis and number of starts in the preparation before the first episode of epistaxis. The significant predictors of recurrence of epistaxis were: change in distance between previous start and start at which the second episode occurred and a change in percentage of winning starts, although the odds ratios were low (0.98–0.99). Conclusions Females experience epistaxis at a younger age than males. No readily applicable predictors of the recurrence of epistaxis were identified.